The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pntd.0005803
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and optimization of Theileria parva sporozoite full-length p67 antigen expression in mammalian cells

Abstract: Delivery of various forms of recombinant Theileria parva sporozoite antigen (p67) has been shown to elicit antibody responses in cattle capable of providing protection against East Coast fever, the clinical disease caused by T. parva. Previous formulations of full-length and shorter recombinant versions of p67 derived from bacteria, insect, and mammalian cell systems are expressed in non-native and highly unstable forms. The stable expression of full-length recombinant p67 in mammalian cells has never been des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 41 publications
(48 reference statements)
2
14
1
Order By: Relevance
“…However, p67C had several advantages over the full-length protein when expressed in E. coli , such as better stability and higher expression yields [13] , [15] . A very recent study has demonstrated stable expression of p67 without the transmembrane domain in mammalian cells [23] . It will be interesting to determine the efficacy of this antigen in vaccine trials.…”
Section: Discussionmentioning
confidence: 99%
“…However, p67C had several advantages over the full-length protein when expressed in E. coli , such as better stability and higher expression yields [13] , [15] . A very recent study has demonstrated stable expression of p67 without the transmembrane domain in mammalian cells [23] . It will be interesting to determine the efficacy of this antigen in vaccine trials.…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts to express recombinant T. parva proteins in prokaryotic or eukaryotic systems for vaccine purposes have been challenging and the process has been hindered due to protein insolubility and misfolding, among other issues (15, 16, 20). Recently, we were able to express full-length T. parva p67 antigen in mammalian cells and demonstrated that the recombinant antigen retained its immunogenic properties (21). Considering the technical and biological challenges associated with the expression of Theileria sp.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly with the identification of novel antigens was extensive work to optimize antigen expression systems and delivery platforms for Theileria antigens. Both prokaryotic and eukaryotic systems have been tested for expression of potential T. parva vaccine antigens (15, 16, 20, 21). Codon usage, post-translational modifications, protein conformation, and solubility are a few aspects that have been considered in deciding the most suitable platform to express antigens for subunit vaccines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the NheI/SmaI cut amplicons were cloned into the shuttle vector pINT2EGFP (25) and cut with the same enzymes, generating pCMV-tPA-MMP, pCMV-tPA-MMP-5mut, and pCMV-tPA-MMP-2mut, thereby placing the tPA-MMP ORFs under the transcriptional control of the immediate early gene promoter of human cytomegalovirus (CMV), followed by the bovine growth hormone polyadenylation signal (pA). Alternatively, the NheI/SmaI cut amplicons were subcloned into the vector pEF1α-p67 (26) to put the tPA-MMP ORFs under the transcriptional control of the Human Elongation Factor 1 Alpha (EF1α) promoter followed by the bovine growth hormone pA, thus generating pEF1α-tPA-MMP, pEF1α-tPA-MMP-5mut, and pEF1α-tPA-MMP-2mut.…”
Section: Sequence Analysis and Cloning Of Mmpmentioning
confidence: 99%